2002
DOI: 10.1016/s0002-9440(10)64199-5
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Tumor Necrosis Factor-α in Remodeling the Splenic Marginal Zone during Leishmania donovani Infection

Abstract: The development of secondary lymphoid organs is a highly regulated process, mediated by tumor necrosis factor (TNF) family cytokines. In contrast, the mechanisms controlling changes in lymphoid architecture that occur during infectious disease are poorly understood. Here we demonstrate that during infection with Leishmania donovani, the marginal zone of mice undergoes extensive remodeling, similar in extent to developmental abnormalities in mice lacking some TNF family cytokines. This process is selective, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(168 citation statements)
references
References 55 publications
6
160
1
1
Order By: Relevance
“…This functional role for the FRC network, when taken in conjunction with our prior finding that the FRC network is remodeled during experimental VL (22), is entirely consistent with the observation that T cell migration into the periarteriolar lymphocytic sheath (PALS) is severely impaired in mice with VL (19). Mice with progressive VL also have defective traffic of DCs into the PALS, although this functional defect reflects IL-10-induced inhibition of CCR7 expression, rather than the defective production of CCL21 and CCL19 that occurs as a consequence of loss of the FRC network (22).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This functional role for the FRC network, when taken in conjunction with our prior finding that the FRC network is remodeled during experimental VL (22), is entirely consistent with the observation that T cell migration into the periarteriolar lymphocytic sheath (PALS) is severely impaired in mice with VL (19). Mice with progressive VL also have defective traffic of DCs into the PALS, although this functional defect reflects IL-10-induced inhibition of CCR7 expression, rather than the defective production of CCL21 and CCL19 that occurs as a consequence of loss of the FRC network (22).…”
Section: Discussionsupporting
confidence: 88%
“…Quantitative analysis demonstrated that there was a significant increase in the frequency of CD31 + vessels with accompanying α-SMA + mesenchymal cells (14 dpi, 32% ± 5% of all CD31 + cells; 28 dpi, 90% ± 4%; Figure 3B). The marginal zone sinus also undergoes some disruption during experimental VL (19). However, we, as well as others working in murine models of malaria (24), noted that MAdCAM-1, the marker usually used to identify marginal sinus lining cells in the spleen, became expressed in a diffuse pattern across the white pulp after infection (Supplemental Figure 1), making it difficult to quantify changes in the marginal sinus with any degree of certainty.…”
Section: Splenomegaly In Experimental Vl Is Accompanied By Extensive mentioning
confidence: 86%
See 1 more Smart Citation
“…Early infection is accompanied by rapid IL-12 production by DC [12], the activation of CD4 + and CD8 + T cells, and the subsequent production of a variety of Th1 and Th2 cytokines, including IL-2, 14]. While this immune response can readily eliminate most L. donovani amastigotes from the liver of infected mice over a 50-100-day period [15], parasites persist in the spleen, and this persistence is associated with severe splenomegaly and an array of pathological changes to the splenic lymphoid microenvironment [16][17][18]. Little is known, however, about T cell dynamics in this highly inflammatory environment, although previous studies have indicated an increase in the rate of apoptotic CD4 + and CD8 + T cells during the later stages of infection [19].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, proliferation of DO11 cells may be triggered by TCR-independent cytokine-mediated mechanisms. TNF-a, IL-2, IL-4 and IFN-c are all upregulated during chronic infection [13,14,18] and have been implicated in antigen-independent proliferation of human [35] and murine [36,37] memory CD4 + T cells. However, the action of bystander cytokines alone is unlikely to explain our data, as such a model would have also predicted the expansion of DO11 cells in L. donovani-infected mice in the absence of OVA, something we have not observed.…”
mentioning
confidence: 99%